The Politics of Christianity in Shaping the Political Dynamics of Zambia - Timalizge Zgambo (Religions)
Religion can often be very influential in the political system and political actors frequently take advantage of the leverage that it provides. In the Zambian case, Christianity in particular plays a crucial role in politics and policymaking, dating from the pre- to post-colonial era. Around 1880, Zambia, then Northern Rhodesia, became a British colony and, at the same time, Christianity was introduced within the context of the European culture. Later, 27 years after independence, Zambia was declared a Christian nation, and all Zambian political leaders have embraced Christianity as the nation’s identity. Thus, Christianity plays a critical function in Zambia’s political sphere. The main aim of this paper is to critically examine how Christianity seeks to direct the political agenda in Zambia’s national politics. It demonstrates the interplay between church and state relations linked to how the state seeks to govern the nation in a Godly manner and the implications on public policymaking in Zambia. This paper explores a multifaceted analysis of the existing literature and the ideas around the politics of the state and religion. It argues that (i) Christianity in Zambia is often used as a political weapon to gain political mileage and (ii) Christianity as a religion has been traditionalised in Zambia. It serves as a “national moral campus”, which compromises the nation’s position as a so-called “democratic” state and suppresses individual freedoms. Thus, it corrupts the very nature of fundamental practices of the religion itself, as it has simply blossomed into more of a norm than a religion. Understanding these dynamics is very crucial, especially in the context of how religion is perceived, experienced and exercised in the political arena to circumvent limited policy options for broader problem solving.